TRAINING ON THE PROCEDURES FOR REJUVENATING EGGPLANT PLANTS IN GAMPONG BINJEE, NISAM SUB-DISTRICT - Faliza, Nur; Fahrizal, Effan; Fitri, Cut Azmah; Alamsyah, Rizki; Farhan, Fauzan (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2022)
North Aceh has many potential natural resources, one of that is the potential horticultural crops. Apart of being fishermen, people in North Aceh also works as farmers, breeders and gardeners. One of the villages where most of the people work as a gardener is Binjee Village, Nisam Sub-District. One of plants that mostly grown is eggplant. Eggplant is one the superior food ingredients that is easy to grow and the prize is cheap. However, this plant is often being damaged and dies quickly, sometimes also difficult to bear fruit. High consumption of eggplant as a cheap and easy food ingredient makes the gardeners unable to meet the markets need due to the mentioned problems. Based on these problems, its necessary to have an effort to provide an alternative solution that can increase the eggplant productions. One of the solutions is increasing the yield by rejuvenating plants. Rejuvenating aims as a special treatment for old plants to be able to bear the fruits again as well as increasing the yield. The results obtained are media publication, collaboration between Malikussaleh University and Binjee Village, and publication in scientific journals. This community service also positively impacted on the Binjee Village in increasing the eggplant yields. Keywords: Eggplant, Rejuvenating, Gardeners.